The ultimate CSS reference - O'Brien, Paul. (Collingwood, Vic. : Sitepoint, 2008)
A first reference book will be simultaneously released online and in print in order to get publicity, user buy-in, and interaction. A well thought out presentation and organization of the book will ensure that the information is as quick to access, and easy to scan.
Keywords: Cascading style sheets